KAJIAN BIBLIOMETRIK: TREN RISET PENDIDIKAN PSIKOLOGI ISLAM DALAM PANGKALAN DATA SCOPUS - Mufidah Sukriyani; Istanto Istanto; Muhamad Subhi Apriantoro; Afief El Ashfahany; Luthfi Afif Murtadho (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
Bibliometric indicators are one of the tools that play a role in evaluating the results of scientific research; examining the interaction between science and technology, producing mapping of the field of science, tracking/tracing the development of new knowledge in a particular field, and are future indicators in making strategic plans. This study aims to determine the mapping of the development and direction of Islamic educational psychology research in publications indexed in the Scopus database. This research uses bibliometric analysis techniques to explore all publications indexed in the Scopus database on Islamic educational psychology from 1983 to 2023. The data obtained were analyzed using Excel and R/R-Studio. VOSviewer was used to perform a visual analysis of keyword occurrences and document citations together. The author found 161 publications that matched the function, subject, and criteria set. The results showed an annual growth rate of 2.78. The bibliometric analysis conducted was limited to Scopus data. The limitation of this research is that it only takes metadata of Scopus-indexed publications. Other national and international databases were not taken into account in this study. This study provides a brief overview of the literature that can be accessed by researchers working in the field of Islamic psychology education and provides recommendations for research.